The Effect of Spirit at Work and Compensation toward Employee Performance in PT. Arista Auto Lestari Medan - Pribadi, Teddi; Effendi, Ihsan; Suryani, Wan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to determine the "Effect of Work Spirit and Compensation on Employee Performance at PT. Arista Auto Lestari Medan ". The type of data used is associative, which is a study that asks the relationship between two variables. The population in this study were all employees at PT. Arista Auto Lestari Medan as many as 65 people. Data collection techniques in the form of distributing questionnaires to office employees at PT. Arista Auto Lestari Medan. Data analysis techniques using validity and reliability, hypothesis testing, statistical tests using multiple linear analysis models using multiple linear analysis models and determination tests.Â  The results of the t test can be seen that the t count on the morale variable is 4.147 greater than t table of 1.689 with a probability of t that is sig 0.004. Based on these values, the morale variable has a positive and significant effect on performance variables and the value of t arithmetic oversight is 6,649 greater than t table of 1,689 with a sig level of 0,000 smaller than the significance limit of 0.005, the partial compensation variable has a positive and significant effect on performance variable. Based on the results of the F test, the F value of 42.567 is greater than the F table of 3.27, which means that morale and compensation simultaneously have a positive and significant effect on performance variables. The R Square value obtained is 0.727. This figure shows that 72.7% of performance (the dependent variable) can be explained by morale and compensation. The remaining 27.3% is influenced by other factors not explained in this study.